Relationship between SNPs and expression level for candidate genes in rheumatoid arthritis. (January 2015) - Fodil, M; Teixeira, VH; Chaudru, V; Hilliquin, P; Bombardieri, S; Balsa, A; Westhovens, R; Barrera, P; Alves, H; Migliorin, P; Bardin, T; Cornelis, F; et al.
<x xml:space="preserve">Abstract</x> Objectives: The study of polymorphisms of genes differentially expressed may lead to the identification of putative causal genetic variants in multifactorial diseases such as rheumatoid arthritis (RA). Based on preceding transcriptomic results, we genotyped 10 single nucleotide polymorphisms (SNPs) belonging to six genes (S100A8, RNASE2, PGLYRP1, RUNX3, IL2RB, and LY96) showing the highest fold change (> 1.9) when level of expression was compared between RA patients and controls. These SNPs were then analysed to evaluate their role in RA. Method: The relationship between gene expression and genotypes of SNPs was first investigated by Kruskal–Wallis and Mann–Whitney tests in RA patients and controls. The genetic association of these SNPs with RA were then analysed using family-based association tests in trio families. Results: We found that RNASE2 gene expression was related to rs2013109 genotypes in 14 RA patients (p = 0.030). The association study in a discovery sample of 200 French trio families revealed a significant association with RA for one SNP, PGLYRP1-rs2041992 (p = 0.019); this association was stronger in trios where RA patients carried the HLA-DRB1 shared epitope (SE) (p = 0.003). However, this association was not found in a replication sample of 240 European trio families (p = 0.6). Conclusions: Family-based association tests did not reveal an association between RA and any SNP of the candidate genes tested. However, RNASE2 gene expression was differentially expressed in RA patients considering a sequence polymorphism. This result led us to highlight the potential disease-specific regulation for this candidate gene in RA.